The Relationship Between Conformity and Brand Switching Intention on Adolescent Handphone Brand - Fajriyah, Syarifah; Komarudin, Komarudin (Prosiding University Research Colloquium, 2021)
This study aims to determine the relationship between conformity with brand switching intentions of cellphone brands among adolescents in Sungailiat Bangka district. The hypothesis in this study is that there is a positive relationship between conformity with brand switching intentions of cellphone brands in adolescents. Subjects in this study were 190 adolescents in Sungailiat Bangka sub-district, aged 16-21 years. The data collection process in this study used two scales; they are conformity scale and brand switching intention scale. The conformity scale consisted of 46 items while the brand switching intention consisting of 45 items. The data analysis technique used the product-moment correlation technique to find out more about the relationship between the independent variables, namely conformity and dependent variables, namely the intention of brand switching. The researcher found that the calculation result of r ^ 2 was 0.999 with a percentage of 99.9% and a p-value of 0.000.